Effectiveness of Pelvic Rocking Exercise with Birth Ball on the Duration of Third Stage of Labor - Karningsih; Mardeyanti; Yulfitria, Fauziah; Sari, Dewi Nirmala; Purwanti, Dwi (International Journal of Science and Society, 2024)
The method involving pelvic rocking exercises using a birth ball combined with acupressure represents a strategy in midwifery aimed at easing tension in the pelvic muscles, beneficial for shortening the length of labor, particularly in its third stage. This approach significantly enhances uterine contractions by prompting the pituitary gland to release oxytocin, thereby aiding in the swift expulsion of the placenta. The objective of this study is to evaluate the comparative effectiveness of pelvic rocking exercises with a birth ball and SP6 acupressure on shortening the third stage of labor. The Research design was Quasi-Experimental with Two Group Comparison, and the research was conducted in a maternity clinic in East Jakarta. The Respondents of this study were women in the active phase of the first stage of Labor. Participants and Sampling Technique: The total sample size was 64 respondents, divided into two groups of 32 each. The initial group underwent an intervention involving pelvic rocking exercises using a birth ball, whereas the second group was treated with SP6 acupressure. The method of selection used was purposive sampling, enabling the investigators to choose subjects according to predefined eligibility criteria. The Results were analyzed using bivariate analysis with the Mann-Whitney U test, as all variables were found to have non-normal distributions. The study findings indicated a statistically significant difference in the duration of the third stage of labor between the group that received the pelvic rocking exercise with a birth ball and the group that underwent the Acupressure SP6 intervention, as shown by a p-value of 0.005 (< 0.05). The data analysis demonstrated that the group participating in the pelvic rocking exercise with a birth ball experienced a quicker third stage of labor, with an average rank of 26.38, in contrast to the acupressure SP6 group, which had an average rank of 38.63. Therefore, it can be concluded that employing the pelvic rocking exercise with a birth ball is an effective method for reducing the length of the third stage of labor, proving to be a safe option for expecting mothers.